POLITIK KEBIJAKAN PENDIDIKAN AGAMA DAN KEAGAMAAN: REVITALISASI UPAYA PEMERINTAH TERHADAP PENDIDIKAN KEAGAMAAN - Ahmad Syafii; Siti Qurrotul A’yuni (Tadrib: Jurnal Pendidikan Agama Islam, 2019)
Indonesia is the biggest archipelago country in the world, the government has tried to prosper the people by issuing policies on regional autonomy. Regional autonomy in its development is widespread in all fields, one of them in education. Autonomy Education gained much support among the people, thus giving birth to Decentralization of Education, namely to give up government responsibility according to the needs and capabilities of each region. The effort has been regulated in Law Number 20 Year 2003 on National Education System supported by Government Regulation no. 55 of 2007. However, these efforts have not been fully realized, so that sometimes cause gap and prolonged criticism. Therefore we as a policy-bearer must prioritize the principle good governance in Decentralization of Education. The religious and religious education policies contained in Government Regulation No. 55 of 2007 are intended to help realize the goals of education in Indonesia, giving the right of autonomy in the form of decentralization of education to each school in each region to manage the institution. If the school is religious based, it is given the freedom to manage according to the teachings of the religion. But to realize this policy requires strong observers and willing to act, the principle of autonomy, flexibility, participatory and initiative can be used as a basis in realizing these goals as a whole.